Monitoring A Fluid Circuit: A Comparison between Arduino UNO and PIC - Perjaru, C; Preduşcă, G; Miruna Avram; Radu, M; Stănescu, C (The scientific bulletin of Electrical Engineering Faculty, 2023)
The purpose of this project is to design an electrical circuit for measuring specific parameters, such as liquid level and engine RPM, to monitor a fluid circuit. The project involves a comparison between the Arduino Uno development platform and the PIC16 development platform. The devices utilized include a level sensor, motor potentiometer, ultrasonic sensor (HC-SR04), submersible pump, a 4x20 LCD (Liquid Crystal Display) with an I2C (Inter-Integrated Circuits) interface, and various connection cables.